2011
DOI: 10.1002/ldr.1126
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality and Spatial Variability Assessment of Land Use Effects in a Typic Haplustoll

Abstract: Soil management practices can have negative or positive effects on soil quality. Our objective was to assess the effect of long-term agricultural practices by evaluating selected soil physical and chemical properties. Soil samples were collected from two depths (0 to 15 and 15 to 30 cm) within a native pasture and an adjacent agricultural field that was being used for three different crop rotations. Soil quality was quantified using aggregate stability, bulk density, soil texture and available water content as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 18 publications
2
37
0
Order By: Relevance
“…Moreover an integrated index is essential for quantitative comparison of different soils. Several indices have been proposed to assess soil quality, which were mostly microbial in nature and for agricultural soils (Sharma et al, 2005;Masto et al, 2007aMasto et al, , 2008aOzgoz et al, 2013;Sinha et al, 2009;Morugán-Coronado et al, 2013;van Leeuwen et al, 2015). Indexing involves three main aspects: (1) choosing appropriate indicators for a minimum data set, (2) transforming the indicators to scores, and (3) combining the scores into an index (Sinha et al, 2009).…”
Section: R E Masto Et Al: Assessment Of Environmental Soil Qualitymentioning
confidence: 99%
“…Moreover an integrated index is essential for quantitative comparison of different soils. Several indices have been proposed to assess soil quality, which were mostly microbial in nature and for agricultural soils (Sharma et al, 2005;Masto et al, 2007aMasto et al, , 2008aOzgoz et al, 2013;Sinha et al, 2009;Morugán-Coronado et al, 2013;van Leeuwen et al, 2015). Indexing involves three main aspects: (1) choosing appropriate indicators for a minimum data set, (2) transforming the indicators to scores, and (3) combining the scores into an index (Sinha et al, 2009).…”
Section: R E Masto Et Al: Assessment Of Environmental Soil Qualitymentioning
confidence: 99%
“…It is well known that soil organic matter, especially humic materials, is cementing agents in soil particles; however, certain organic components can paradoxically play a role as a dispersion element in claywater systems (Tarchitzky et al, 1993). Reduced input rate of organic matter and translocation of surface soils with water erosion are also reasons for low organic matter content of cultivated soils (Ozgöz et al, 2013). Lower organic carbon content in farmland caused a significant difference in aggregate stability values (Ozgöz et al, 2013).…”
Section: Effects Of Different Rates Of Humic Acid (Ha) Applications Omentioning
confidence: 99%
“…Reduced input rate of organic matter and translocation of surface soils with water erosion are also reasons for low organic matter content of cultivated soils (Ozgöz et al, 2013). Lower organic carbon content in farmland caused a significant difference in aggregate stability values (Ozgöz et al, 2013). Shanmuganathan and Oades (1983) reported that addition of anions to soils causes dispersion in clay fraction associated with decreas- ing isoelectric point, and it is known that especially fulvic acids are the most efficient anions.…”
Section: Effects Of Different Rates Of Humic Acid (Ha) Applications Omentioning
confidence: 99%
“…The topographic factor has been traditionally included in the study of the spatial distribution of soil properties (Fernández-Calviño et al, 2013;Haregeweyn et al, 2013;Ozgoz et al, 2013;Wang and Shao, 2013). Over time, many researchers have quantified the relationships between topographic parameters and soil properties such as soil OM and physical properties such as particle size distribution, bulk density and depth to specific horizon boundaries (McKenzie and Austin, 1993;Gessler et al, 1995Gessler et al, , 2000Pachepsky et al, 2001;Ziadat, 2005).…”
Section: Introductionmentioning
confidence: 99%